Analisis Teori Paradigma (Paradigm Theory) Hans Kung Dalam Kajian Agama: An Analysis of Hans Kung’s Paradigm Theory in Religious Study - Che Nordin, Mohd Khairul Naim (Afkar: Jurnal Akidah dan Pemikiran Islam, 2018)
Scientific advancement shows the emergence of a modified scientific theory to function in explaining the religious and social phenomena of its adherents. Among these examples is the development of a paradigm theory that was originally introduced by Thomas Kuhn for the field of natural science but later duplicated with some changes by Hans KÃ¼ng for religious studies. This paper aims to explain the theory of religious paradigm according to KÃ¼ng in particular on the methodological aspects, the framework and its features. Through descriptive qualitative methods involving inductive approach, the paper finds that this theory highlights the interpretation of religion in the aspect of historiography and cultural values and norms in turn overruns the more comprehensive and constructive aspects of the combination study of textual, contextual and dogmatic or religious beliefs and the practice of its adherents.